The role and importance of using technology in teaching - Gaxhiqi, Behxhet (Technium Social Sciences Journal, 2023)
This study aims to make an in-depth analysis of the prevalence and nature of the phenomenon of Internet use in teaching. The selected grades are grades VI to grade IX which in the literature are known as lower secondary education. The researcher has used the mixed method model, including qualitative and quantitative research strategies. The study involved n = 164 students and n = 117 teachers from eleven 9-year schools in the city of Prishtina, and n = 117 school staff. The results from the questionnaires with students that are quantitative in nature showed that the use of the Internet in schools is an integral part of the schools taken in the study. Most of the teachers stated that they had not received training to deal with the new models of application of technologies in teaching and a considerable part of them stated that they were unsure how to react in case an obstacle appeared in the non-functioning of technology during the lesson. The sample selected in the research consists of a total of 281 respondents, of which 117 were teachers and 164 students. There are a total of 117 employees and leaders of educational institutions and 164 students who will serve as samples.